Commercial Culture, Political Culture and the Political Economy of Trade Policy: The Case of Japan - Seiichi Katayama; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2000)
In this paper we present a model of endogenous trade-policy formation which captures crucial aspects of the Japanese commercial and political culture. We analyze the influence of the portrayed cultural traits and show that cultural idiosyncrasies are important determinants of trade policy formation; especially the complex interaction of the two types of cultures is shown to have significant consequence for the policy outcome. Contrasting our model's behavior with the stylized facts of Japanese politics, we arrive at the conclusion that the model's behavior is compatible with the observed (trade) policy positions held by Japanese politicians over the last fifty years.
Keywords: 330